Optical quantum positioning method based on random resampling of scattering free path - Mu ZHOU; Jing ZHANG; Yong WANG; Xiaolong YANG; Lingxia LI (Tongxin xuebao)
To solve the problem that the quantum signal was disturbed by the scattering environment, which lead to large fluctuation of the positioning error and poor positioning robustness, an optical quantum positioning method based on random resampling of the scattering free path was proposed.The scattering model was established based on the Monte Carlo theory, and the scattering free path matrix was constructed by combining the environment information and coincidence counting results.The scattering free program was resampled, and the relative distance error of different light sources in different time groups was calculated.Based on that, the light sources were dynamically selected, and the position of the target object was estimated.Experimental results show that the positioning error of the proposed method can achieve the centimeter level, and the confidence probability of the positioning error within 0.12 m is 90.57%.